EDUKASI MANFAAT LATIHAN PEREGANGAN SEBAGAI UPAYA PENCEGAHAN KELUHAN MUSCULOSKELETAL DISORDERS (MSDs) PADA PENGRAJIN ANYAMAN BAMBU DESA MOJOREJO PONOROGO - Mohammad Muslih; Rindang Diannita; Nuraini; Lathiefa Rusli; Bambang Setyo Utomo; Ahmad Ma’ruf Muzaidin Arrosit; Maya Tsuroya Alfadla (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2024)
Abstract Musculoskeletal Disorders (MSDs) are disorders related to the nervous system, ligaments, muscle tissue, tendons, cartilage, bone structure and blood vessels. Musculoskeletal Disorders (MSDs) are an occupational disease whose symptoms can include pain, swelling, and even numbness. The aim of this Community Service is an effort to increase craftsmen's understanding of the risks of Musculoskeletal Disorders (MSDs), as well as education on the urgency of stretching exercises as a preventive measure to prevent work-related diseases. The method used in this Community Service is Participatory Action Research (PAR) which was carried out on bamboo woven craftsmen in Mojorejo Village, Jetis District, Ponorogo Regency, East Java. The Community Service activity program includes stretching exercises together with Mojorejo Village Bamboo weaving craftsmen, as well as Occupational Safety and Health training. The results of this Community Service are increased understanding regarding Musculoskeletal Disorders (MSDs) and Occupational Safety and Health, as well as education regarding stretching exercises, so that craftsmen can stretch independently to improve physical fitness and prevent work-related diseases. Keywords: Occupational Safety and Health, Stretching Exercises, Musculoskeletal Disorders (MSDs) Abstrak Musculoskeletal Disorders (MSDs) adalah gangguan yang berkaitan dengan sistem syaraf, ligamen, jaringan otot, tendon, kartilago, struktur tulang, dan pembuluh darah. Musculoskeletal Disorders (MSDs) merupakan salah satu penyakit akibat kerja dengan gejalanya dapat berupa nyeri, bengkak, bahkan mati rasa. Tujuan Pengabdian kepada Masyarakat ini adalah sebagai upaya meningkatkan pemahaman pengrajin terhadap risiko Musculoskeletal Disorders (MSDs), serta edukasi urgensi dari latihan peregangan sebagai salah satu langkah preventif mencegah penyakit akibat kerja. Metode yang digunakan pada Pengabdian kepada Masyarakat ini adalah Participatory Action Research (PAR) yang dilakukan pada pengrajin anyaman bambu di Desa Mojorejo, Kecamatan Jetis, Kabupaten Ponorogo, Jawa Timur. Program kegiatan Pengabdian kepada Masyarakat antara lain latihan peregangan bersama dengan pengrajin anyaman bambu Desa Mojorejo, serta pelatihan Keselamatan dan Kesehatan Kerja. Hasil dari Pengabdian kepada Masyarakat ini adalah peningkatan pemahaman terkait Musculoskeletal Disorders (MSDs) dan Keselamatan dan Kesehatan Kerja, serta edukasi terkait latihan peregangan, agar pengrajin dapat secara mandiri melakukan peregangan untuk meningkatkan kebugaran jasmani dan mencegah penyakit akibat kerja. Kata Kunci: Keselamatan dan Kesehatan Kerja, Latihan Peregangan, Musculoskeletal Disorders (MSDs)